Laser-material interaction through digital light processing - Liau, Wi Zardson. (2013)
DLP technology is based on an optical semiconductor, called a Digital Micromirror Device (DMD), which uses mirrors made of aluminium to reflect light to make a picture. The DMD is often referred to as the DLP chip. The chip can contain more than 2 million tiny mirrors, about the size of a typical pixel in our smart phones today. The mirrors are laid out in a matrix, with each mirror representing one pixel. It was invented by Dr. Larry Homback and Dr William E. “Ed” Nelson of Texas Instruments (TI) in 1987 [1]. However, the application of DMD among industries is still minor.